PENAMPILAN KARKAS AYAM PEDAGING DENGAN PEMBERIAN KULIT KOPI (Coffea sp) PENGOLAHAN SEDERHANA SUBSTITUSI SEBAGIAN JAGUNG DENGAN LEVEL YANG BERBEDA - Antarani, Indriani; Laihad, J.T.; Poli, Z.; Montong, P.R.R.I. (Universitas Sam Ratulangi, 2020)
CARCASS PERFORMANCE OF BROILER FED RATION CONTAINING COFFEE (Coffea sp) HUSK WASTE PRODUCT TREATED BY SIMPLE PROCESSING AND SUBSTITUTING PARTS OF CORN WITH DIFFERENT LEVELS. Broilers had rapid growth rate and need high nutrient protein and energy balance in the diet. This study was conducted to evaluate the use of coffee husk waste product treated by simple processing substituted with part of corn in ration on carcass percentage of broiler. Study was applied at Faculty of Animal Science, Sam Ratulangi University during 35 days. Total of 144 day old chick unsexed broilers, strain of CP 707, involving 36 experimental units of battery pens were used in this study. Each unit of pen was filled 4 birds under completely randomized design on factorial patter of 3x4. Factor A was focused on three processing treatments including coffee husk heated under sun light (A1), coffee husk immersed in the water (A2), and coffee husk boiled under water (A3). Factor B was focused on four treatments of substitution levels including ration containing corn without coffee husk substitution (B0), ration containing corn substituted with 25% coffee husk (B1), ration containing corn substituted with 50% coffee husk (B2), ration containing corn substituted with 75% coffee husk (B3). Variables observed were including percentages of thigh, wing, breast and back part. Analysis of variance showed that interaction of processing treatments did not affect significantly on the percentages of thigh, wing, breast and back part. This study indicated that simple processing of coffee husk were not affected the carcass percentages of broiler. The substitution levels significantly affected carcass percentage of broiler. Percentages of thigh, wing, breast and back part were 28.92%-30.98%, 10.38%-12.68%, 35.10%-38.55% and 19,68%-22,71%, respectively. This study showed that utilization of coffee husk waste product by above simple processing could substitute part of corn in ration of 25% producing high carcass percentage of broiler.Keywords: Coffee husk by product, broiler part of carcass percentage